FREE RADICAL SCREENING ACTIVITY OF MARINE SPONGE AURORA GLOBOSTELLATA - M, Sugappriya; D, Sudarsanam (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Marine sponges are sessile organisms which produce chemicals to prevent themselves from the predators; these chemicals are the secondary metabolites. These metabolites are said to contain various biological activities. A research has been made for analyzing the antioxidant activity of crude extracts of sponges using hexane, ethyl acetate, ethanol, water as solvents and compared using gallic acid as standard antioxidant. Methods: The free radical scavenging activity was analyzed using 1,1-diphenyl-2-picryl-hydrazyl (DPPH) free radical. Results: The significant radical scavenging activity shown by hexane extract with inhibitory concentration IC as 30.62 µg/ml which is nearby the activity of gallic acid with IC 50 50 18.93 µg/ml. The method is based on the spectrophotometric measurement of the DPPH concentration change resulting from the reaction with an antioxidant. Conclusion: Therefore, based on the analysis the hexane extract of the sponge has shown to have more antioxidants may be due to the presence of phenols and flavonoids. The research can be further done by the isolation of the antioxidant compound through chromatographic techniques, which could come up with the isolation of novel compound for various therapeutics. Keywords: 1,1-diphenyl-2-picryl-hydrazyl, Chemo preventive, Absorbance, Cytotoxic, Antioxidant, Aurora globostellata.